Advances in transportation geotechnics II : proceedings of the 2nd International Conference on Transportation Geotechnics (2nd ICTG), Hokkaido, Japan, 10-12 September 2012 - International Conference on Transportation Geotechnics (2nd : 2012 : Hokkaido, Japan); Miura, Seiichi, editor (Leiden, The Netherlands : CRC Press, 2012)
Includes bibliographical references and index